Liberalización financiera y sus efectos en el crecimiento económico de Colombia para el periodo 1980-201 (2013)
During the last decades, the Colombian economy has liberalized its capital account, its stock market and its national financial system in order to accelerate the pace of economic growth. It was taken for granted that Colombia suffered from a deep scarcity of capital and an inefficient functioning of domestic banking and financial intermediaries. The empirical evidence shows that despite the intensity of these reforms, the pace of economic growth in the country is neither higher nor more stable. This paper argues that the country's poor macroeconomic performance is due to the fact that financial liberalization has not led to further financial deepening, and its benefits have not been taken advantage of due to the country's institutional weakness.